2007
DOI: 10.1093/ajcn/85.2.530
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet during pregnancy in relation to eczema and allergic sensitization in the offspring at 2 y of age

Abstract: Background: Maternal diet during pregnancy might be one of the factors that influences fetal immune responses associated with childhood allergy. Objective: We analyzed the association between maternal diet during the last 4 wk of pregnancy and allergic sensitization and eczema in the offspring at 2 y of age. Design: Data from 2641 children at 2 y of age were analyzed within a German prospective birth cohort study (LISA). Maternal diet during the last 4 wk of pregnancy was assessed with a semiquantitative food-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(132 citation statements)
references
References 33 publications
(28 reference statements)
4
123
1
1
Order By: Relevance
“…Moreover, the growth of airways during pregnancy or childhood may be vulnerable to oxidative exposures, while suboptimal antioxidant status during this critical period might result in oxidative airway damage, reductions in airway compliance or both (7) . In contrast to the data above on antioxidants, two recent birth cohorts reported that a higher intake of vitamin C and citrus fruits in pregnancy was associated with an increased risk of early eczema and allergic sensitisation, respectively (9,10) .…”
Section: Dietary Hypothesesmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, the growth of airways during pregnancy or childhood may be vulnerable to oxidative exposures, while suboptimal antioxidant status during this critical period might result in oxidative airway damage, reductions in airway compliance or both (7) . In contrast to the data above on antioxidants, two recent birth cohorts reported that a higher intake of vitamin C and citrus fruits in pregnancy was associated with an increased risk of early eczema and allergic sensitisation, respectively (9,10) .…”
Section: Dietary Hypothesesmentioning
confidence: 65%
“…In animal models, vitamin E, zinc and vitamin D have been shown to modify fetal lung development, and vitamin E, zinc, vitamin D and PUFA can modulate T-cell responses. In humans, birth cohort studies have reported associations between wheezing and eczema in early life and low prenatal status of selenium and iron (17) , low maternal intake of vitamin E (9,18,19) , vitamin D (20,21) , apple and fish (10,22,23) .…”
Section: Maternal Diet During Pregnancymentioning
confidence: 99%
“…These observations are in contrast to results from previous studies, which mainly, but not consistent, suggest that maternal fish intake during pregnancy protects against the development of childhood asthma and atopy. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Observational studies in large cohorts observed lower incidence of eczema in offspring of mothers with the highest fish consumption during pregnancy, 19,21 but not lower incidences of wheezing or asthma. In the Netherlands, fish consumption is relatively low, which can explain the differences in the observations.…”
Section: Maternal Fish Consumption and Atopic Symptoms Etm Leermakersmentioning
confidence: 99%
“…7 Many observational and interventional studies, explored the associations of maternal fish consumption or fish oil supplementation during pregnancy with the risks of childhood asthma and atopy. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Although these studies showed a protective effect on at least one outcome, they were not all able to adjust for potential confounders. Also, previous intervention studies differed in selection of participants, types of intervention and definition of outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrients most commonly proposed to contribute to the aetiology of atopic diseases are fatty acids and antioxidants. While protective effects of fatty acid composition and intake of antioxidants have been reported (1)(2)(3)(4) , some studies do not confirm these findings (5) . Clarification on the implication of food intake during infancy and childhood on allergic diseases needs to be sought, and this relies on the application of accurate methods to assess food intake.…”
mentioning
confidence: 95%